2014
DOI: 10.1016/j.aquatox.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The biological effects of antidepressants on the molluscs and crustaceans: A review

Abstract: Antidepressants are among the most commonly detected human pharmaceuticals in the aquatic environment. Since their mode of action is by modulating the neurotransmitters serotonin, dopamine, and norepinephrine, aquatic invertebrates who possess transporters and receptors sensitive to activation by these pharmaceuticals are potentially affected by them. We review the various types of antidepressants, their occurrence and concentrations in aquatic environments, and the actions of neurohormones modulated by antide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
162
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(168 citation statements)
references
References 128 publications
1
162
0
5
Order By: Relevance
“…Perhaps fluoxetine, through modulation of serotonin levels, stimulates crab activity levels and drives aggressive behaviors. Fluoxetine's effect on serotonin levels appears to increase boldness and potentially other risk behaviors as studies on other species have suggested (Dzieweczynski & Hebert, 2012; Fong & Ford, 2014; Mesquita et al., 2011; Pedetta et al., 2010; Tierney & Mangiamele, 2001). …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Perhaps fluoxetine, through modulation of serotonin levels, stimulates crab activity levels and drives aggressive behaviors. Fluoxetine's effect on serotonin levels appears to increase boldness and potentially other risk behaviors as studies on other species have suggested (Dzieweczynski & Hebert, 2012; Fong & Ford, 2014; Mesquita et al., 2011; Pedetta et al., 2010; Tierney & Mangiamele, 2001). …”
Section: Discussionmentioning
confidence: 88%
“…Serotonin and serotonin analogs have been shown to alter agonistic behaviors (McPhee & Wilkens, 1989; Tierney & Mangiamele, 2001) and activity levels (Fong & Ford, 2014; Perez‐Campos, Rodriguez‐Canul, Perez‐Vega, Gonzalez‐Salas, & Guillen‐Hernandez, 2012) in crustaceans. Fluoxetine concentrations ≄120 Όg/L caused a stimulation of locomotor behavior in the crab Carcinus maenas (Mesquita et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still some argument as to whether it is more applicable as a biomarker of oestrogen exposure rather than effect [69]. There is also a growing concern over psychoactive drugs because they are designed to alter (human) behaviour and have side effects that could also influence fitness-related traits in free-living animals [11,15,55,70] (table 1 and §6). Recalling the 'read-across' hypothesis ( §3), there are a number of reasons why compounds designed to have therapeutic effects in humans and livestock could impact nontarget animals and ecosystems: there is strong evolutionary conservation of drug targets across phyla; pharmaceuticals are generally highly potent, and long term, low-level exposure due to their continual release to the environment is likely to lead to chronic effects; for some pharmaceuticals, mode of action is associated with a potentially harmful effect (e.g.…”
Section: Pharmaceuticals As Environmental Contaminants Of Concernmentioning
confidence: 99%
“…Despite these examples, there has been a notable lack of studies that demonstrate effects of APIs based on ecologically relevant assessments, with respect to appropriate exposure concentrations and duration, ecotoxicological endpoints and implications of mixture effects [7,8]. However, where ecologically appropriate exposures were used, APIs have been demonstrated to cause effects in organisms, such as behaviour and reproduction, which may have broader ecological consequences [7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%